Business schools in crisis - Fred Phillips; C. H. Hsieh; C. Ingene; Lonnie Golden (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Economic, political, and demographic changes, technological advances, two crashes of the economy, ethical scandals, and other developments in the business environment have strained the roles and enrollments of American universities' business schools. The b-schools have not responded adequately. Prevailing theories in many of the management disciplines have broken down, partly as a result of the same environmental changes. Again, schools and curricula have not adapted. Collegiate business education is in dire crisis. In this paper we document the crisis, note measures that have been taken - both constructive and otherwise - and make further suggestions for improving the situation.
Keywords: 650; Business education; MBA; Business schools; Management; Ethics